Mycosis fungoides and Sézary syndrome: clinical presentation, diagnosis, staging, and therapeutic management - Denis Miyashiro; José Antonio Sanches (Frontiers in Oncology, 2023)
Mycosis fungoides (MF) and Sézary syndrome (SS) are cutaneous T-cell lymphomas. MF is the most common cutaneous lymphoma, and it is classified into classic Alibert-Bazin MF, folliculotropic MF, pagetoid reticulosis, and granulomatous slack skin, each with characteristic clinical presentation, histopathological findings, and distinct clinical behaviors. SS is an aggressive leukemic variant of cutaneous lymphoma, and it is characterized by erythroderma, lymphadenopathy, and peripheral blood involvement by malignant cells. There is a wide range of dermatological manifestations of MF/SS, and prompt recognition is essential for early diagnosis. Skin biopsy for histopathology and immunohistochemical analysis is imperative to confirm the diagnosis of MF/SS. Histopathology may also provide information that may influence prognosis and treatment. Staging follows the TNMB system. Besides advanced stage, other factors associated with poorer prognosis are advanced age, male gender, folliculotropism in histopathology of patients with infiltrated plaques and tumors in the head and neck region, large cell transformation, and elevated lactate dehydrogenase. Treatment is divided into skin-directed therapies (topical treatments, phototherapy, radiotherapy), and systemic therapies (biological response modifiers, targeted therapies, chemotherapy). Allogeneic bone marrow transplantation and extracorporeal photopheresis are other treatment modalities used in selected cases. This review discusses the main clinical characteristics, the histopathological/immunohistochemical findings, the staging system, and the therapeutic management of MF/SS.